In-patient mental health care from the asylum system to the present day : a lived experience of policy and practice - Colley, Andrew (Teacher) (Routledge, 2024)
"With a focus on the progression and dismantlement of the Asylum system, this book examines key issues around the policy and practice of in-patient mental health provision in the UK, making comparisons with similar services in other parts of the world. Part narrative history and critical analysis, part autoethnography, this unique volume critiques the ethics of early policy decisions which led to the closure of the old Victorian asylums and the advent of care in the community, identifying continuing issues of institutionalisation, containment, and segregation. Drawing parallels with the continuing dilemmas of 'inclusion' in other areas of public policy and provision, chapters discuss controversial issues such as the response to the Covid pandemic, the influence of 'anti-psychiatry', and the continuing use of electro convulsive therapy. Ultimately, the book makes a vital theoretical and practical contribution to the continuing debate around in-patient mental health care in the 21st century. The book will be of interest to academics, researchers and policy makers in the fields of healthcare policy and history of mental health provision more broadly. Psychiatrists interested in the history of the asylum system in the UK, as well as present day mental health professionals will also find the book of use"-- Provided by publisher.
Keywords: Psychiatric hospital care -- Great Britain -- History.; Psychiatric hospital patients -- Great Britain -- History.; Mental illness -- Treatment -- Great Britain -- History.; Mental health services -- Great Britain -- History.; elektronické knihy; electronic books